Control strategies for nitrous oxide emissions reduction on wastewater treatment plants operation. (15th November 2017) - Santín, I.; Barbu, M.; Pedret, C.; Vilanova, R.
Abstract: The present paper focused on reducing greenhouse gases emissions in wastewater treatment plants operation by application of suitable control strategies. Specifically, the objective is to reduce nitrous oxide emissions during the nitrification process. Incomplete nitrification in the aerobic tanks can lead to an accumulation of nitrite that triggers the nitrous oxide emissions. In order to avoid the peaks of nitrous oxide emissions, this paper proposes a cascade control configuration by manipulating the dissolved oxygen set-points in the aerobic tanks. This control strategy is combined with ammonia cascade control already applied in the literature. This is performed with the objective to take also into account effluent pollutants and operational costs. In addition, other greenhouse gases emissions sources are also evaluated. Results have been obtained by simulation, using a modified version of Benchmark Simulation Model no. 2, which takes into account greenhouse gases emissions. This is called Benchmark Simulation Model no. 2 Gas. The results show that the proposed control strategies are able to reduce by 29.86% of nitrous oxide emissions compared to the default control strategy, while maintaining a satisfactory trade-off between water quality and costs. Graphical abstract: Highlights: Nitrous oxide reduction in the secondary wastewater treatment. Effluent quality and operational costs are also taken into account. Two cascade control strategies are combined in order to achieve all objectives. Benchmark Simulation Model No 2 Gas is used for simulation.